Exploring the Effects of Vitamin D Supplementation on Cognitive Functions and Mental Health Status in Subjects Under Methadone Maintenance Treatment. Issue 1 (January 2020) - Ghaderi, Amir; Rasouli-Azad, Morad; Farhadi, Mohammad Hassan; Mirhosseini, Naghmeh; Motmaen, Maryam; Pishyareh, Ebrahim; Omidi, Abdollah; Asemi, Zatollah
Abstract : Objectives: Vitamin D deficiency may be linked to several mental complications including cognitive deficits, depression, and anxiety in patients under methadone maintenance treatment (MMT). This study was designed to explore the effect of vitamin D supplementation on cognitive functions and mental health parameters in subjects under MMT. Methods: This randomized, double-blinded, placebo-controlled clinical trial was carried out among 64 patients under MMT. Participants were randomly allocated to receive either 50, 000 IU vitamin D supplements (n = 32) or placebo (n = 32) every 2 weeks for 24 weeks. Cognitive functions and mental health parameters were taken at baseline and posttreatment to evaluate relevant variables. Results: After the 24-week intervention, compared with the placebo, serum 25(OH) vitamin D levels significantly increased in participants who received vitamin D supplements (β 14.50; 95% confidence interval [CI], 13.17–15.83; P  < 0.001). In addition, compared with the placebo, subjects who received vitamin D had a significant reduction in Iowa Gambling Task (β −6.25; 95% CI, −8.60 to −3.90; P  < 0.001), and significant increases in Verbal Fluency Test (β 2.82; 95% CI, 0.78–4.86; P  = 0.007), Immediate Logic Memory (β 1. 32; 95% CI, 0.27–2.37; P  = 0.01), Reverse Digit Span (β 2.06; 95% CI, 1.18–2.94; P  < 0.001) and visual working memory (β 0.75; 95% CI, 0.33–1.16; P  = 0.001). Also, vitamin D supplementation significantly improved BDI (β −2.76; 95% CI, −3.97 to −1.55; P  < 0.001) compared with the placebo. When we applied Bonferroni correction, LM-Immediate ( P  = 0.07) became nonsignificant, and other mental health parameters did not alter. Conclusions: Overall, taking 50, 000 IU vitamin D supplements every 2 weeks for 24 weeks by patients under MMT had beneficial effects on cognitive functions and some mental health parameters. Further studies are needed to confirm our findings.